Consumer preference and behaviour of Islamic home financing : a study of potential home buyers in Malaysia - Hanudin Amin
Consumer preference has been a missing component in the development of Islamic home financing products. The views of consumers on the existing and new Islamic home financing products are generally overlooked by Islamic banks, although they are one of the most important stakeholders of Islamic banks. This issue has been evidently observed when Islamic home financing products are often criticized by the customers. Exploring factors which can improve consumer preference will offer a new understanding on customers' preference for Islamic home financing. Drawing upon the theory of planned behaviour (TPB), the innovation diffusion theory (IDT) and the theory of interpersonal behaviour (TIB), this study proposes a model to examine consumer preference for Islamic home financing as opposed to other types of financing. The role of attitude and religious satisfaction as a mediator and a moderator, respectively are also examined. The model is tested using survey data from 760 respondents who are the employees of public universities in Malaysia. Universities are selected because they have a good mix of respondents both covering professional and non-professional groups, reflecting the actual mix of bank customers of Islamic banks. The data are later analyzed using Partial Least Squares (PLS) since this method is appropriate when the model developed is complex and it is also used for the purpose of theory development. This study finds that product range, financial benefit, service quality, Islamic bankers' knowledge and the perceived risk of Islamic home financing are instrumental in determining consumer preference of Islamic home financing. Moreover, maqasid consumer index is a powerful predictor of consumer preference of Islamic home financing. It is also reported that Islamic bankers' knowledge, perceived risk of Islamic home financing and Islamicity of debt policy are instrumental in determining consumers' attitude. On the same note, consumer religiosity is found to be a key predictor of attitude. Attitude and religious satisfaction are evidently proven as significant mediator and moderator, respectively. In addition, information search is instrumental in influencing the consumer affective factor towards the Islamic home financing preference. The current study findings offer valuable insights for managers of Islamic banks to plan Islamic home financing offerings effectively. Findings of this study offer guidelines and benchmark which can help bank managers to formulate new approaches to further improve consumer preference of Islamic home financing products. The model of the current study addresses the interrelationship between the variables, thereby providing a better understanding of consumer preference. It provides fresh perspectives on the effects of critical success factors and consumer factors on consumer preference. Similarly, new perspectives are also found as these factors are also the determinants of consumers' attitude, and thus add to the negligible literature on how different factors influence consumers' attitude. It also offers new perspectives on the role of religious satisfaction as a moderator and the role of attitude as a mediator, often neglected in prior Islamic home financing literature.